Qualified dating and common-law marriage: A necessary differentiation - Rodrigues, Edwirges Elaine; Alvarenga, Maria Amália de Figueiredo Pereira (Seven Editora, 2024)
In view of the numerous transformations faced by Family Law, over time, the stable union has been legally recognized as a family entity, and for this purpose, it is enough to fulfill its characterizing elements determined by the legislator. On the other hand, the institute of qualified dating has acquired new contours, becoming the target of jurisprudential and doctrinal discussions, which began to highlight the differences between stable union and the so-called qualified dating, mainly seeking to avoid the possible confusion of legal effects between such institutes. Thus, through the deductive method, a review of the specialized bibliography in Family Law related to the institutes of stable union and qualified dating was carried out, seeking to outline the main element responsible for differentiating them, that is, the animus familiae, in addition to pointing out the effects produced by them and discussing the validity of the dating contract. DOI:https://doi.org/10.56238/sevened2023.006-130